Invective Vocabulary in The Language of the Ukrainian Mass Media During the Russia-Ukraine War: Stylistic Layers and Pragmatics of Meaning - Navalna, Maryna; Kostusiak, Nataliia; Sazonova, Yaroslava; Prosianyk, Oksana; Skliarenko, Olesia; Chernobrov, Yuliia; Ovsiienko, Alla; Pryimachok, Oksana; Shynkar, Tetiana (My University, 2024)
In scientific research, the invective vocabulary of the period of the Russia-Ukraine war (2022–2023) was analyzed using the language material of the Ukrainian mass media. The corpus of collected material gave reasons to single out the following groups and subgroups of invectives: 1. Personal: 1) immorality, humiliation of dignity and qualities; 2) assessment of mental abilities; 3) assessment of physical characteristics and invective designations of a person's appearance. 2. Social: 1) immorality of relations, such as lies, fraud; 2) manipulative actions regarding social processes, personalities, etc.; 3) invectives of social origin and status, political views, etc. As evidenced by the collected mass media material of the period of the Russia- Ukraine war (2022–2023), in the language of modern Ukrainian journalism, invectives of various kinds are widely used, which give a negative assessment mostly to the leaders of the aggressor country or those politicians who support the Russia-Ukraine war, and as well as citizens who are on the side of the military invasion. Under the influence of extra-linguistic factors – the Russia-Ukraine war – we traced the trend towards actualization of offensive vocabulary in the language of the Ukrainian mass media. Invectives mostly give the language of the mass media a negative assessment: they convey contempt for the invaders and especially for their politicians.
Keywords: Ukrainian language; mass media language; journalism; invective vocabulary; negative evaluation; stylistic role; literary norms; non-linguistic factors; Russian-Ukrainian war